Video-Assisted Thoracoscopic Internal Rib Fixation. Issue 5 (May 2022) - Castater, Christine; Hazen, Ben; Davis, Carolyn; Hoppe, Samuel; Butler, Caroline; Grant, April; Archer-Arroyo, Krystal; Maceroli, Michael; Todd, S. Rob; Nguyen, Jonathan
Rib fractures result in serious morbidity and mortality after trauma. Although there is ongoing debate about surgical rib fixation, it is increasingly important for some patients. Minimally invasive techniques for rib fixation are gaining traction within the trauma community. We present an observational experience at our level 1 trauma center with our first 10 cases of video-assisted thoracoscopic surgery (VATS) internal rib fixation. Video-assisted thoracoscopic surgery internal plates are especially helpful for rib fractures under the scapula, which are difficult to access traditionally. This technique is also excellent at reducing complex segmental fractures as the bridge can span across multiple fractures with a single post on either side. They also work well for posterior fractures where multiple screws cannot be placed. Video-assisted thoracoscopic surgery internal rib fixation is a viable and exciting option for surgical fixation. The plates work particularly well for certain fracture patterns.